2012
DOI: 10.1038/icb.2012.69
|View full text |Cite
|
Sign up to set email alerts
|

IL‐7 downregulates IL‐7Rα expression in human CD8 T cells by two independent mechanisms

Abstract: Interleukin (IL)-7 is an essential nonredundant cytokine, and throughout the lifespan of a T-cell signaling via the IL-7 receptor influences cell survival, proliferation and differentiation. It is therefore no surprise that expression of the IL-7 receptor alpha-chain (CD127) is tightly regulated. We have previously shown that IL-7 downregulates expression of CD127 at the cell surface and now elucidate the kinetics of that suppression and demonstrate that IL-7 downregulates CD127 transcripts and surface protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 55 publications
(85 reference statements)
6
34
1
Order By: Relevance
“…Initially we attempted to identify in vitro -derived ILC subsets using surface marker expression similar to how we identified these ILC subsets ex vivo (Figure 1 and Figure S1); however, consistent with our and others’ prior observations, we noted that surface antigen expression following in vitro differentiation was not perfectly concordant with what is observed when evaluating SLT ILCs ex vivo (Ahn et al, 2013; Freud et al, 2005; Freud et al, 2006). For instance, while all non-NK ILCs from SLT expressed CD161 and CD127 ex vivo (Hazenberg and Spits, 2014), we only detected CD161 but not CD127 expression following culture of SLT Lin − CD34 + CD45RA + progenitor cells (Figure 3B and data not shown), consistent with previous reports (Ahn et al, 2013; Ghazawi et al, 2013; Vranjkovic et al, 2007). In addition, we rarely detected or did not detect other ILC subset-associated surface antigens, including CD294 and ST2 (Mjösberg et al, 2011), among Lin − CD161 + ILCs derived in vitro (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…Initially we attempted to identify in vitro -derived ILC subsets using surface marker expression similar to how we identified these ILC subsets ex vivo (Figure 1 and Figure S1); however, consistent with our and others’ prior observations, we noted that surface antigen expression following in vitro differentiation was not perfectly concordant with what is observed when evaluating SLT ILCs ex vivo (Ahn et al, 2013; Freud et al, 2005; Freud et al, 2006). For instance, while all non-NK ILCs from SLT expressed CD161 and CD127 ex vivo (Hazenberg and Spits, 2014), we only detected CD161 but not CD127 expression following culture of SLT Lin − CD34 + CD45RA + progenitor cells (Figure 3B and data not shown), consistent with previous reports (Ahn et al, 2013; Ghazawi et al, 2013; Vranjkovic et al, 2007). In addition, we rarely detected or did not detect other ILC subset-associated surface antigens, including CD294 and ST2 (Mjösberg et al, 2011), among Lin − CD161 + ILCs derived in vitro (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…By inducing receptor internalization and translocation from early endosomes to the proteasome, IL-7 directly influences its receptor density on the cell surface and thus regulates the intensity of its own signaling cascades. 29,[31][32][33][34][35][36][37][38] Whereas downregulation of CD127 following IL-7 stimulation may allow more cells access to this survival cytokine, 35,37 it may also provide negative feedback allowing the cell to regulate the number of available receptors and thus the intensity and duration of IL-7 signaling. Interleukin-7 (IL-7) is a pivotal cytokine essential to T-cell development, survival and function.…”
mentioning
confidence: 99%
“…[4][5][6][7] Upregulation of the anti-apoptotic molecule Bcl-2 by IL-7 8-12 provides a major contribution to cell survival. 33,36,43 We have previously shown that IL-7 downregulates CD127 expression in primary human CD8 T cells by two independent mechanisms. IL-7 both stimulates proliferation of CD8 T cells in a time-and dose-dependent manner [13][14][15][16] and upregulates the expression of perforin 17 and CD25, the IL-2 receptor alpha-chain.…”
mentioning
confidence: 99%
“…Decrease in CD127 may be directly associated with T-cell activation in HIV infection, and has previously been correlated with HIV disease progression [46,47]. Further, co-infection may harness an advanced stage of immune deterioration where survival of T cells is significantly affected [48][49][50]. We also showed that CD127 expression was inversely associated with surrogate markers of disease progression, immune activation markers and CD57, suggesting the essential role of CD127 in maintaining T-cell homeostasis and survival [8].…”
Section: Discussionmentioning
confidence: 94%